Fig. 1 in Helminth Diversity In Teleost Fishes From The South Orkney Islands Region, West Antarctica - Kuzmina, T. A.; Salganskiy, O. O.; Vishnyakova, K. O.; Ivanchikova, J.; Lisitsyna, O. I.; Korol, E. M.; Kuzmin, Yu. I. (Zenodo, 2022)
Fig. 1. Proportion (%) of four parasite taxa in three fish species from the South Orkney Islands area, West Antarctica. Published as part of Kuzmina, T. A., Salganskiy, O. O., Vishnyakova, K. O., Ivanchikova, J., Lisitsyna, O. I., Korol, E. M. & Kuzmin, Yu. I., 2022, Helminth Diversity In Teleost Fishes From The South Orkney Islands Region, West Antarctica, pp. 135-152 in Zoodiversity 56 (2) on page 141, DOI:10.15407/zoo2022.02.135, http://zenodo.org/record/7175665